DC MOTOR SPEED CONTROL USING PID CONTROL WITH ENCODER AS FEEDBACK - Muhammad Reza Aditya Nurkholis Putera; Rahmat Hidayat (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
PID controllers are widely used to improve system response , as they offer clear, simple functionality and ease of deployment and use. One of the important roles of the PID controller can be seen in its application to control and stabilize the angular velocity in the reference value of a direct current (DC) motor. The purpose of this task is to implement a PID controller as a DC motor speed controller so that it can understand the characteristics of each PID controller parameter on the system response curve. The test results show that each PID value parameter (Proportional, Integral, Derivative) has different characteristics to the system response. For example, adding the Kp parameter can reduce the steady-state error, reduce the rise time, but can increase the overshot value. Meanwhile, adding the Ki parameter can affect the increase in overshot, reduce the rise time, and reduce or even almost eliminate the steady state error value. Then, adding the Kd parameter can reduce the overshot, reduce the rise time, and increase the undershot